Soil Rejuvenation By Natueco Science : A Boon To Crop And Animal Husbandry. - Suchde , Deepak; Dhanotia , R.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
An on farm trial on Natueco-Science (recently developed system of crop husbandry ) was carried out for six years . In this study it was found that in the Amrut Mitti ie. fertile live soil. the available forms of all major elements and micronutrients increased many folds. Also record yield of various crops were obtained. The proximate composition of bottle gourd showed that protein and calcium increased significantly and also Vitamin B12 was recorded at the level of 3 mg /100g which was found in BDL market sample of bottle gourd. Further 5 mg /100g Vitamin B12 in Drumstick was recorded.
Keywords: Amurt Jal; Amrut Mitti Fertile live soil; Soil rejuvenation; Natueco Science; Available nutrients